2009
DOI: 10.5194/acpd-9-13629-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid formation of isoprene photo-oxidation products observed in Amazonia

Abstract: Abstract. Isoprene represents the single most important reactive hydrocarbon for atmospheric chemistry in the tropical atmosphere. It plays a central role in global and regional atmospheric chemistry and possible climate feedbacks. Photo-oxidation of primary hydrocarbons (e.g. isoprene) leads to the formation of oxygenated VOCs (OVOCs). The evolution of these intermediates affects the oxidative capacity of the atmosphere (by reacting with OH) and can contribute to secondary aerosol formation, a poorly understo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 52 publications
2
39
1
Order By: Relevance
“…Other studies have shown also minor (Fares et al, 2015) or negligible (Karl et al, 2009 emission of MVK/MACR; however, in these studies there was a net uptake to the leaf. Part of the MVK/MACR concentration and fluxes may also be misattributed fragments from higher oxygenated hydrocarbons (Liu et al, 2013;Rivera-Rios et al, 2014).…”
Section: Mvk/macr and Their Sourcescontrasting
confidence: 60%
“…Other studies have shown also minor (Fares et al, 2015) or negligible (Karl et al, 2009 emission of MVK/MACR; however, in these studies there was a net uptake to the leaf. Part of the MVK/MACR concentration and fluxes may also be misattributed fragments from higher oxygenated hydrocarbons (Liu et al, 2013;Rivera-Rios et al, 2014).…”
Section: Mvk/macr and Their Sourcescontrasting
confidence: 60%
“…The products MVK and MACR have been studied in many atmospheric environments both by proton transfer reaction mass spectrometry (PTR-MS) and gas chromatography (GC) (21). Large data sets are available (7,8,21,22). By comparison, ambient measurements of ISOPOOH isomers are sparse, and available data sets are limited to temperate regions (23,24).…”
Section: Significancementioning
confidence: 99%
“…These HPALDs can easily undergo photolysis and lead to additional production of OH and also HCHO. Despite some minor refinement to the scheme [ Peeters and Müller , 2010], owing to issues raised by the studies of Karl et al [2009], Paulot et al [2009a], and Archibald et al [2010b], the LIM0 mechanisms potentially represents the best option for realistic simulation of the Amazonian atmosphere, though it sill needs extensive evaluation. For example, the low‐NO x HCHO yields are largely unknown owing to uncertainties in the isomerization reaction rates and HPALD photolysis products; the formation of HPALDs also partially suppress MVK and MACR production.…”
Section: Discussionmentioning
confidence: 99%